Electronic Publishing: Costing Model and Copyright - Bhatia, Ketki; Rawal, C. N. (Journal of Information and Knowledge, 2007)
Due to rapid changes in communication technology, publications are also published in electronic form, but they have to face some problems out of which one is cost and secondly copyright act. Costing models are shown which includeds the direct and indirect costs along with how to calculate the cost. Copyright law was originally formed to cope with the printing press. It has been partially modified to the take account of the electronic age. Some suggestions are given in this regard.